2022
DOI: 10.3390/jcm11113052
|View full text |Cite
|
Sign up to set email alerts
|

Monthly Follow-Ups of Functional Status in People with COPD: A Longitudinal Study

Abstract: Functional status is an important and meaningful outcome in people with chronic obstructive pulmonary disease (COPD), although its measurement is not embedded in routine clinical assessments. This study described the functional status of people with COPD using the 1-min sit-to-stand test (1minSTS) over a 6-month period and the examined sociodemographic and clinical characteristics associated with this outcome. Data from a prospective study including people with COPD were analyzed. Functional status was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…These results on the 1 M STST are supported in an extensive systematic review from 2019, where the 1 M STST is recommended, especially in settings where time and space are limited 36 . A recent study from 2022 also found that having a follow-up using the 1 M STST also had a clinically relevant benefit on functional status in people with COPD 41 .…”
Section: Results-phase Twomentioning
confidence: 94%
“…These results on the 1 M STST are supported in an extensive systematic review from 2019, where the 1 M STST is recommended, especially in settings where time and space are limited 36 . A recent study from 2022 also found that having a follow-up using the 1 M STST also had a clinically relevant benefit on functional status in people with COPD 41 .…”
Section: Results-phase Twomentioning
confidence: 94%
“…Similar characteristics in people with functional impairment have been previously reported. 7 , 67 , 68 Because most of these characteristics are preventable and modifiable, attention to interventions in this population should be given. In fact, different stakeholders have stated that people with functional impairment should be prioritized to pulmonary rehabilitation, 69 and these programs have shown to be effective in improving the FC of people with COPD.…”
Section: Discussionmentioning
confidence: 99%